“Like Fiction, Only Considerably More Dangerous”: South Asia and Anxieties about Nuclear Surveillance in Twenty-First Century Indo-American Geopolitical Thrillers - Kar, Souvik; Roy, Dibyadyuti; Bhattacharjee, Shuhita (Surveillance & Society, 2026)
This article investigates twenty-first-century literary depictions of contestations between the nuclear surveillance infrastructures of two of the largest democracies in the world—the United States and India. Recognizing that these disputes have shaped US-India relations since Indian independence from colonial British rule in 1947, this article examines how themes of deception—central to Cold War spy fiction—appear in contemporary literary works about surveillance conflicts between the two nations. These texts reflect mutual distrust: American surveillance portrays India as an irresponsible postcolonial nuclear power, while Indian countersurveillance depicts the US as a hypocritical and coercive hegemon who enables Pakistan’s nuclear program. With reference to these strategic conflicts over the politics and logic of knowledge about nuclear materials, infrastructures, bodies, ideas, and motivations, this article critically analyzes representative texts: an American novel and an Indian novel series—the American diplomat Matthew Palmer’s novel Secrets of State (2015) and the Indian novelist Shaunak Agarkhedkar’s tetralogy Let Bhutto Eat Grass (2017–2022). In revealing behind-the-scenes machinations of nuclear surveillance, this article highlights how literary productions are key cultural conduits for underscoring the importance of mutual trust in nuclear politics. Such trust, as the texts examined here show, requires moving beyond the rigid cycle of hiding and exposing secrets that has long characterized—and may still define—the tense relationship between two nuclear democracies, the United States of America and India.